PRAWO NA LITWIE NA PRZEŁOMIE XVIII I XIX WIEKU - Godek, Sławomir (Zeszyty Prawnicze, 2016)
LAW IN LITHUANIA AT THE TURN OF THE 19TH CENTURY Summary In the Polish and international literature, there is an almost complete absence of work which covers the issue of the history of the Third Statute of Lithuania after the Partitions of the Commonwealth directly, as a separate research problem. On this issue, there are only hints in papers of extremely different natures on the widest variety of specific questions. There is a long way to go before we have a reasonably complete image of the fate of the Statute in the post-Partition era. It would seem that papers on this question should move in a number of basic directions. The starting point should be a comprehensive study of the legal acts issued after the Partitions for the Lithuanian and Rus lands of the former Commonwealth, in order to track the changes which introduced them to the law of the time. One great challenge will be to understand judicial practice in the West and Northwest guberniyas in the Empire. It would also be worth looking more closely at the codification work conducted in the Białystok Region which gave rise to the drawing up of a project based on the Lithuanian Statute. In the same context, it is also worth studying the almost unknown Polish work on the Western Code drawn up in the years 1830-1837. One crucial issue which is still waiting for a researcher is the role of the Third Lithuanian Statute in legal teaching in the eastern territories of the former Commonwealth at the turn of the 19th century, and especially in centres like Vilnius, Krzemieniec and Połock.